1990
DOI: 10.1073/pnas.87.17.6808
|View full text |Cite
|
Sign up to set email alerts
|

Purification to homogeneity and partial characterization of cytotoxic lymphocyte maturation factor from human B-lymphoblastoid cells.

Abstract: A cytokine that can synergize with interleukin 2 to activate cytotoxic lymphocytes was purified to homogeneity. The protein, provisionally called cytotoxic lymphocyte maturation factor (CLMF), was isolated from a human Blymphoblastoid cell line that was induced to secrete lymphokines by culture with phorbol ester and calcium ionophore. The purification method, utilizing classical and high-performance liquid chromatographic techniques, yielded protein with a specific activity of 8.5 x 107 units/mg in a T-cell g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
323
1
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 595 publications
(337 citation statements)
references
References 22 publications
7
323
1
2
Order By: Relevance
“…7 IL12 is among the most effective cytokines for stimulating antitumor immunity. 8,9 It enhances the proliferation and lytic activity of Th1/Tc1 T cells and natural killer cells, in part by inducing the expression of cytokines, such as IFNg. 10 The in vivo antitumor activity of IL12 is also mediated by induction of IFNg and by inhibition of angiogenesis.…”
mentioning
confidence: 99%
“…7 IL12 is among the most effective cytokines for stimulating antitumor immunity. 8,9 It enhances the proliferation and lytic activity of Th1/Tc1 T cells and natural killer cells, in part by inducing the expression of cytokines, such as IFNg. 10 The in vivo antitumor activity of IL12 is also mediated by induction of IFNg and by inhibition of angiogenesis.…”
mentioning
confidence: 99%
“…6,7 This cytokine is a key participant in a variety of immune activities including the stimulation of T cells and natural killer (NK) cells and the regulation of cell adhesion molecules. [6][7][8] In addition to its immune-stimulating capacity, IL-12 has also been shown to be antiangiogenic.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 This cytokine is a key participant in a variety of immune activities including the stimulation of T cells and natural killer (NK) cells and the regulation of cell adhesion molecules. [6][7][8] In addition to its immune-stimulating capacity, IL-12 has also been shown to be antiangiogenic. 9 Significant antitumor activity has been demonstrated in several animal models, [10][11][12] and clinical trials have indicated the potential antitumor activity of this cytokine.…”
Section: Introductionmentioning
confidence: 99%
“…IL-12 [16][17][18][19][20] augments proliferation and cytotoxic activity of T and NK cells, induces IFN-␥ production and facilitates T helper type 1 (Th1) response. In vivo administration of rIL-12 to mice not only induces specific CTL response, 21 but also results in reduction of experimental pulmonary and hepatic metastases of various tumors.…”
Section: Introductionmentioning
confidence: 99%